Evaluating the efficiency of some chemical compounds and biotic agents in controlling the disease of root decay caused by Fusarium Solani on pepper - Entesar Marzoog Hussein (Zien Journals, 2022)
The results of using isolation from the roots of pepper plants revealed symptoms of disease such as browning of the roots and rotting of a portion or the complete root caused by Fusarium solani fungus, as well as from all fields within the city of Babylon. The results of testing the effect of isolation on radish seeds revealed that the entire isolations testing of F. solani fungi resulted in a momentous reduction in the germination percentage under the probability level of 0.05, which ranged between 0% - 37% compared to the comparison treatment (with no pathogenic fungi), which was 100%. The findings showed that P. fluorecsens bacteria had a high inhibitory efficiency against an isolation of the pathogenic fungus F.solani (F.s2, Fs3 and Fs4) at a concentration of 5 × 107 (colony formation unit/ml), where the inhibition percentage was 82%, 67.77% and 75.22%, respectively compared to the comparison treatment in which the inhibition rate was 0. Beltanol pesticide achieved an inhibition rate of 100% with all isolations on PDA culture media. Also, all the treatments used, which include Pseudomonas fluorescen, Penicillium corylyphilium and salicylic acid, gave the best results in decreasing the infection with F. solani and with significant differences between them and the fungus treatment alone, where the treatment of bacteria fluorescens.P + P. corylyphilium, the infection severity of the fungus F. solani was less, as it reached 5% in comparison to the treatment of the pathogenic fungus alone, by 80%. As for the treatment of the bacteria fluorescens.P + p.corylyphilium together with the presence of the pathogenic fungus and in the absence of the pathogenic fungus, the highest value in length and fresh and dry weight of the vegetative and root groups, reached 28.50 and 48.50 cm, 52.50, 7.07, 44.00, and 5.03 g, correspondingly, in comparison to the treatment of pathogenic fungi alone. The average length and fresh and dry weight of the vegetative and root groups reached 18.75 and 26.00 cm 15.5, 2.26, 7.00 and 0.19 g respectively.
Keywords: Pseudomonas fluorescen; Penicillium corylyphilium; Fusarium solani